2012
DOI: 10.1002/ptr.4919
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antioxidant and anti‐inflammatory activity of young shoots of the smoke tree, Cotinus coggygria Scop

Abstract: In this study, we investigated the antimicrobial activity of the young shoots of the smoke tree, Cotinus coggygria Scop., Anacardiaceae. The acetone extract and the derived ethyl acetate fraction effectively inhibited the growth of Gram-positive and Gram-negative bacteria (MIC 25-200 µg/ml), while the chloroform fraction showed pronounced activity against the yeast Candida albicans (MIC 3.12 µg/ml). The ethyl acetate fraction exhibited a significant ferric-reducing ability (10.7 mmol Fe(2+) /g extract), a very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…However, some qualitative and quantitative differences were observed. Thus β-phellandrene, the major component in our sample, has been detected in traces only in one of the studied Serbian S. rigidum [ 6 ]. Instead, α-pinene was a dominant compound (48.5-57.4%), while its content did not exceed 4% in our samples.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…However, some qualitative and quantitative differences were observed. Thus β-phellandrene, the major component in our sample, has been detected in traces only in one of the studied Serbian S. rigidum [ 6 ]. Instead, α-pinene was a dominant compound (48.5-57.4%), while its content did not exceed 4% in our samples.…”
contrasting
confidence: 54%
“…Limonene was absent in the Bulgarian plant, but reached 10% in the Serbian sample. The content of sabinene varied between 6.5 and 39.8% in the different plant parts of S. rigidum of Bulgarian origin, while its amount was 1.4, 4.0 and 5.5% in the Serbian samples, respectively [4][5][6]. The discussed differences could be due to environmental conditions or to existence of chemotypes of this endemic species.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The usage of Eurasian smoke tree is predominantly external and though some authors consider it poisonous [26], it has also been applied orally for treatment of throat infl ammations, paradontosis, gastric and duodenal ulcer, diarrhea [12], diabetes [14] and others. In Serbian folk medicine decoction of the C. coggygria bark has been used against cancer [15]. In Asia the herb is applied against hepatitis and anemia [1].…”
Section: Introductionmentioning
confidence: 99%
“…15 In human studies, CC has been shown to reduce blood pressure levels in hypertensive patients, improve antioxidant status, and decrease risk factors associated with cardiovascular diseases. 16 However, current research on CC is lacking, and the pharmacological effects of CC flavonoids (CCFs) are mostly limited to anticoagulant, hemolytic, and antiliver chemical injuries, with only a few reports regarding anticancer effects. In our previous study, anticancer effects were found in GBM cells by CCFs; however, the exact underlying mechanisms of induction of human GBM cell death remain largely unresolved.…”
Section: Introductionmentioning
confidence: 99%